Research to evaluate the efficiency of the structured teaching programme in terms of knowledge on prevention of sexually transmitted diseases among college students at chosen institutions in Dharwad, Karnataka, INDIA (Journal of Pharmaceutical Negative Results, 2022)
Sex is a natural human function that may be used to express love and other strong emotions and does in fact enable reproduction. However, having a sexual relationship might have unforeseen or detrimental effects. Unintentional pregnancy and sexually transmitted illnesses, such as HIV infection, are two of the main possible health effects of sexual activity. Effective preventative efforts and a nationwide open discussion of these issues can significantly lessen these negative effects.